Fabrication and evaluation of nanocellulose sponge for oil/water separation. (15th June 2018) - Phanthong, Patchiya; Reubroycharoen, Prasert; Kongparakul, Suwadee; Samart, Chanatip; Wang, Zhongde; Hao, Xiaogang; Abudula, Abuliti; Guan, Guoqing
Graphical abstract: Highlights: Superhydrophobic nanocellulose sponge (SA/NC) was simply fabricated. SA/NC sponge showed excellent superhydrophobicity and superoleophilicity. SA/NC sponge was suitable to absorb oil spilled in water. SA/NC sponge was easily recovered by hand squeezing and reused. Abstract: Nanocellulose sponge was fabricated by a facile method: freeze-drying of nanocellulose aqueous suspension to sponge state, following by hydrophobic treatment with stearoyl chloride at 50 °C for 1 h. The obtained nanocellulose sponge showed superhydrophobicity (160° of water contact angle) and superoleophilicity with high protection from water but selective absorption of oil. Its absorption capacities for various kinds of oil and non-polar liquids were 25–55 times higher than its dry weight and exhibited excellent selectivity for absorbing of oil which spilled on the surface of water or underwater with high separation efficiency. This superhydrophobic nanocellulose sponge can be easily recovered by simple squeezing and reused at least 10 cycles with remained high separation efficiency. It is expected that such a biodegradable nanocellulose sponge can be applied to solve the oil spill accident and treat the oily wastewater from households and industries.